Monitoring nanoparticle-mediated cellular hyperthermia with a high-sensitivity biosensor. (December 2014) - Mukherjee, Amarnath; Castanares, Mark; Hedayati, Mohammad; Wabler, Michele; Trock, Bruce; Kulkarni, Prakash; Rodriguez, Ronald; Getzenberg, Robert H; DeWeese, Theodore L; Ivkov, Robert; Lupold, Shawn E
Aim: To develop and apply a heat-responsive and secreted reporter assay for comparing cellular response to nanoparticle (NP)- and macroscopic-mediated sublethal hyperthermia.Materials & methods: Reporter cells were heated by water bath (macroscopic heating) or iron oxide NPs activated by alternating magnetic fields (nanoscopic heating). Cellular responses to these thermal stresses were measured in the conditioned media by secreted luciferase assay.Results & conclusion: Reporter activity was responsive to macroscopic and nanoparticle heating and activity correlated with measured macroscopic thermal dose. Significant cellular responses were observed with NP heating under doses that were insufficient to measurably change the temperature of the system. Under these conditions, the reporter response correlated with proximity to cells loaded with heated nanoparticles. These results suggest that NP and macroscopic hyperthermia may be distinctive under conditions of mild hyperthermia. Original submitted 10 May 2013; Revised submitted 31 October 2013